2020
DOI: 10.3390/cancers12020364
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Scaffolds of Colorectal Cancer Metastases as an Organotypic 3D Model of the Liver Metastatic Microenvironment

Abstract: The liver is the most common site for colorectal cancer (CRC) metastasis and there is an urgent need for new tissue culture models to study colorectal cancer liver metastasis (CRLM) as current models do not mimic the biological, biochemical, and structural characteristics of the metastatic microenvironment. Decellularization provides a novel approach for the study of the cancer extracellular matrix (ECM) as decellularized scaffolds retain tissue-specific features and biological properties. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 45 publications
6
47
0
Order By: Relevance
“…Decellularization describes the treatment of a tissue or whole organ with a series of enzymes and detergents to effectively remove the native cellular content and DNA, while maintaining the ECM network. Decellularized scaffolds are tissue-and function-specific based on their origin and can be combined with different cell populations to create 3D models (423)(424)(425).…”
Section: Discussionmentioning
confidence: 99%
“…Decellularization describes the treatment of a tissue or whole organ with a series of enzymes and detergents to effectively remove the native cellular content and DNA, while maintaining the ECM network. Decellularized scaffolds are tissue-and function-specific based on their origin and can be combined with different cell populations to create 3D models (423)(424)(425).…”
Section: Discussionmentioning
confidence: 99%
“…They found that HT-29 cells grown in cancer-derived matrix had increased proliferation, migration and reduced sensitivity to common chemotherapies. HT-29 cells grown in metastases-derived scaffolds had increased epithelial-to-mesenchymal transition phenotype [ 105 ]. With respect to cancer immunology, Pinto et al demonstrated that, unlike healthy colon matrix, colorectal cancer-derived matrix polarized macrophages to the anti-inflammatory M2 phenotype, enhancing macrophage production of immunosuppressive cytokines [ 106 ].…”
Section: Additional 3d Culture Methodsmentioning
confidence: 99%
“…In this novel in vitro CRC model, we evaluated the activity of specific drugs with the aim to translate it as a preclinical model before chemotherapy administration in patients. We recently demonstrated that the decellularized healthy tissues and neoplastic counterparts were biologically active scaffolds able to support the in vitro cell growth and proliferation [14,18]. The decellularization process enables complete cell removal, maintaining at the same time the tissue architecture and preserving the ECM components [19].…”
Section: Introductionmentioning
confidence: 99%